Hubungan Strategi Promosi Tiktok dengan Minat Beli Konsumen Terhadap Peningkatan Penjualan Mochi - Teza Melani Br Bangun; Nadia Safni Nasution; Fatma Tresno Ingtyas; Lorena Ginting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Technological developments have brought major changes in various aspects of life, including the way businesses market their products. In the food industry, technology acts as a catalyst that accelerates and expands the reach of sales promotion strategies using social media and so on. TikTok is one of the most popular platforms and is used by almost all groups, making it very possible to use it as a promotional medium. This research aims to analyze the relationship between TikTok promotional strategies, consumer buying interest and increased sales of Boss Mochi. The data collection technique used is observation. The population used was 50 people who had seen promotional videos on TikTok and made purchases at Bos Mochi. The data collection technique is carried out by giving a set of questions in the form of a questionnaire to respondents to answer. This research was conducted on Jl. Tuasan No. 180, Sidorejo Hilir, Kec. Medan Tembung, Medan City, North Sumatra 20371. From the results of the test discussion above it can be concluded that the variables of TikTok Promotion Strategy and Consumer Purchase Interest with Increased Mochi sales are interconnected and have a positive relationship with each other. The conclusion is based on this research that TikTok promotion strategy has a positive relationship positive and significant with an increase in consumer buying interest, which ultimately has an impact on increasing sales of Bos Mochi products